2012
DOI: 10.5194/angeo-30-683-2012
|View full text |Cite
|
Sign up to set email alerts
|

Global propagation features of large-scale traveling ionospheric disturbances during the magnetic storm of 7~10 November 2004

Abstract: Abstract. Larger-scale traveling ionospheric disturbances (LSTIDs) were studied using the total electron content (TEC) data observed from global GPS network in the regions of North America, Europe, and East Asia during the magnetic storm of 7∼10 November 2004. 4 LSTID events were detected in North America, 4 in Europe, and 3 in East Asia. The parameters of the 11 LSTID events, such as the propagation azimuth (the angle with respect to north, taking clockwise as positive), horizontal phase velocity and damping … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 28 publications
(45 reference statements)
0
26
0
Order By: Relevance
“…LSTIDs originating from auroral sources usually propagate southwestward in high-latitude regions (Ding et al, 2007(Ding et al, , 2008, and westward deviations from the south seem to be caused by the westward movement of the source region (Hocke and Schlegel, 1996). Song et al (2012) found that westward deviations from south of LSTIDs increased as the LSTIDs propagated from high to middle latitudes due to the Coriolis force. At middle and low latitudes, the Japanese GEONET observation network has found eastwardpropagating in addition to westward-propagating traveling ionospheric disturbances (TIDs) .…”
Section: Introductionmentioning
confidence: 89%
“…LSTIDs originating from auroral sources usually propagate southwestward in high-latitude regions (Ding et al, 2007(Ding et al, , 2008, and westward deviations from the south seem to be caused by the westward movement of the source region (Hocke and Schlegel, 1996). Song et al (2012) found that westward deviations from south of LSTIDs increased as the LSTIDs propagated from high to middle latitudes due to the Coriolis force. At middle and low latitudes, the Japanese GEONET observation network has found eastwardpropagating in addition to westward-propagating traveling ionospheric disturbances (TIDs) .…”
Section: Introductionmentioning
confidence: 89%
“…B r s is the main error source of the ionospheric TEC deriving from GPS observation and could reach up to several units of TEC (TECU, 1 TECU = 10 16 electrons m −2 ) or even larger than the real STEC [ Sardón and Zarraoa , ; Zhang et al ., ]; thus, the effect of this biases must be removed to get the real STEC. Here, we corrected this biases by adjusting the data with those of Global Ionospheric Maps from the Crustal Dynamics Data Information System [ Noll , ], which are interpolated in both space and time [ Ding et al ., ; Song et al ., ].…”
Section: Methodsmentioning
confidence: 99%
“…To be exact, this disturbances propagate southwestward. Many previous studies showed that the propagation of TIDs was not always toward the Equator (Tsugawa et al, 2004;Song et al, 2012). In this paper, we note that the direc- …”
Section: Resultsmentioning
confidence: 64%